'The way that we are collecting and using data has evolved' evaluating the Australian National Stroke Audit programme to inform strategic direction. Issue 1 (24th January 2023) - Lynch, Elizabeth; Laver, Kate; Levy, Tamina; Schultz, Timothy
Abstract : Background: The National Stroke Audit has been used to audit and provide feedback to health professionals and stroke care services in Australia since 2007. The Australian Stroke Clinical Registry was piloted in 2009 and numbers of hospitals participating in the registry are increasing. Considering the changing data landscape in Australia, we designed this study to evaluate the stroke audit and to inform strategic direction. Methods: We conducted a rapid review of published literature to map features of successful data programmes, followed by a mixed-methods study, comprising national surveys and interviews with clinicians and administrators about the stroke audit. We analysed quantitative data descriptively and analysed open-ended survey responses and interview data using qualitative content analysis. We integrated data from the two sources. Results: We identified 47 Australian data programs, successful programs were usually funded by government sources or professional associations and typically provided twice yearly or yearly reports. 106 survey participants, 14 clinician and 5 health administrator interview participants were included in the evaluation. The Stroke Audit was consistently perceived as useful for benchmarking, but there were mixed views about its value for local quality improvement. Time to enter data was the most frequently reported barrier to participation (88% of survey participants), due to the large number of datapoints and features of the audit software. Opportunities to improve the Stroke Audit included refining Audit questions, developing ways to automatically export data from electronic medical records and capturing accurate data for patients who transferred between hospitals. Conclusion: While the Stroke Audit was not perceived by all users to be beneficial for traditional quality improvement purposes, the ability to benchmark national stroke services and use these data in advocacy activities was a consistently reported benefit. Modifications were suggested to improve usability and usefulness for participating sites.